Atmospheric impact of Z- and E-isomers of CF3CHCHC2F5 molecule initiated by OH radicals: Reaction mechanisms, kinetics and global warming potential. (May 2019) - Gour, Nand Kishor; Paul, Subrata; Deka, Ramesh Chandra
Abstract: In this manuscript, we have explored the reaction mechanism, kinetics and global warming potentials of Z- and E-isomers of CF3 CHCHC2 F5 molecule initiated by OH radical to understand its impact on the atmospheric environment. Energy profile diagram for OH-initiated reaction pathways for these two isomers are constructed from the data obtained at M06-2X meta hybrid density functional theory along with aug-cc-pVTZ basis set. The observed potential energy and enthalpy and Gibb's free energy of the reactions suggest that OH-addition to Z- and E-isomers is more feasible than the hydrogen abstraction reactions. The rate coefficients of each reaction channel are evaluated by using conventional transition state theory within the temperature range of 200–350 K. We found that the overall rate coefficient for Z-isomers decreases with the increasing temperature, whereas this value increases for E-isomer with the increasing temperature. The overall rate coefficients for both isomers (Z and E) are fitted to modified Arrhenius three parameters and expressed as koverall(Z) = 9.06 × 10 −21 T 2.20 exp (1054.89 ± 0.93/T) and koverall(E) = 1.09 × 10 −21 T 2.77 exp (394.40 ± 1.52/T) cm 3 molecule −1 s −1 respectively. The calculated rate coefficients and branching ratios for each reaction channels indicate that OH radical addition to unsaturated carbons of Z/E- CF3 CHCHC2 F5 molecules are more dominate to the overall reaction than H-abstraction reactions. Finally, we have estimated atmospheric lifetimes and GWPs of Z- and E-isomers of CF3 CHCHC2 F5 molecule.